May nagmamahal sa iyo ([Quezon City] Star Cinema Production, 2001)
Louella, a domestic helper in Hong Kong, Returns to her hometown to search for the son she gave up for adoption.
VCD
Lorna Tolentino, Gina Pareno, Jaclyn Jose, Claudine Barretto, Ariel Rivera, Stefano Mori.
Keywords: Children, adoption; Family--Phils.; Feature films